Rational Design of Better Hydrogen Evolution Electrocatalysts for Water Splitting: A Review - Liu, Fan; Shi, Chengxiang; Guo, Xiaolei; He, Zexing; Pan, Lun; Huang, Zhen‐Feng; Zhang, Xiangwen; Zou, Ji‐Jun (Advanced science, 2022)
The excessive dependence on fossil fuels contributes to the majority of CO2 emissions, influencing on the climate change. One promising alternative to fossil fuels is green hydrogen, which can be produced through water electrolysis from renewable electricity. However, the variety and complexity of hydrogen evolution electrocatalysts currently studied increases the difficulty in the integration of catalytic theory, catalyst design and preparation, and characterization methods. Herein, this review first highlights design principles for hydrogen evolution reaction (HER) electrocatalysts, presenting the thermodynamics, kinetics, and related electronic and structural descriptors for HER. Second, the reasonable design, preparation, mechanistic understanding, and performance enhancement of electrocatalysts are deeply discussed based on intrinsic and extrinsic effects. Third, recent advancements in the electrocatalytic water splitting technology are further discussed briefly. Finally, the challenges and perspectives of the development of highly efficient hydrogen evolution electrocatalysts for water splitting are proposed. This review presents varieties of representative hydrogen evolution reaction (HER) electrocatalysts benefited from intrinsic and extrinsic design strategies and gives insight into classical/novel descriptors and reaction mechanism to provide the audience with a broad and basic understanding. Moreover, the progress on water‐splitting technology is also discussed. Some invigorating perspectives on the challenges and future directions at the HER field are provided.